1994
DOI: 10.1002/aoc.590080111
|View full text |Cite
|
Sign up to set email alerts
|

Volatile metal and metalloid species in gases from municipal waste deposits

Abstract: We have detected volatile species of silicon, vanadium, arsenic, bromine, tin, antimony, tellurium, iodine, mercury, lead and bismuth in gases released from domestic waste deposits, using inductively coupled argon plasma mass spectrometry (ICPMS). By concurrent aspiration of a multielement standard solution for calibration, the element concentrations in deposit gas are found to be in the range from 0.1 ng m-3 to 10 pg m-3 gas. The global amount of some metal species emitted by this process may be of the order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…The measurements were accomplished in a semicontinuous way by a portable AAS analyser, GARDIS-1A. 28 The estimated TGM concentrations are in accordance with those reported for landfill gases by Hirner et al 13 but lower than those of Feldmann and Hirner. 19 In the latter gases, apart from DMHg, Hg 0 or CH 3 HgCl was proposed to be present also.…”
Section: à3supporting
confidence: 77%
See 1 more Smart Citation
“…The measurements were accomplished in a semicontinuous way by a portable AAS analyser, GARDIS-1A. 28 The estimated TGM concentrations are in accordance with those reported for landfill gases by Hirner et al 13 but lower than those of Feldmann and Hirner. 19 In the latter gases, apart from DMHg, Hg 0 or CH 3 HgCl was proposed to be present also.…”
Section: à3supporting
confidence: 77%
“…In these environments, methane and carbon dioxide are produced which also may facilitate volatilization of trace-element compounds such as organometallics. 13 In sewage treatment facilities the partitioning of mercury between sludge and the effluent water is very high. More than 95% of the mercury is found in the sludge phase.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition to the anthropogenic species tetraethyllead and its mixed methylated counterparts, as well as butylated tin species, 3 many methylated arsenic, 4 antimony, 5 germanium 6 and selenium 7 species can be identified in sediments, freshwater, seawater, and in biota, and as volatile species in different gases. [8][9][10][11] It has therefore been speculated that methylated bismuth compounds occur in the environment as well. 12 2 or BiO is predominant.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also reported methylantimony species in an animal, the snail Stagnicola, from an antimony rich region of Yellowknife, using a headspace HG-GC-MS method. Further reports of methylantimony compounds in the environment concern volatile metalloid species in sewage and landfill fermentation gases [96][97][98][99][100][101], and in hot springs [98]. Me 3 Sb was found in these emissions, with reported concentration ranges for sewage and landfill fermentation gases of 0.62-0.15 and 23.9-71.6 mg Sb m À3 respectively [102].…”
Section: Organoantimony Compounds In the Environmentmentioning
confidence: 98%
“…During the mid 1990s environmentally occurring Me 3 Bi was detected in gases emitted from sewage sludge [96,100] and volatile bismuth species were detected in gases from municipal waste deposits [146]. In later work, Feldmann et al [147] used cryotrapping gas chromatography and HG coupled with an ICP-MS to detect Me 3 Sb in landfill and sewage gas.…”
Section: Organobismuth Compounds In the Environmentmentioning
confidence: 99%